Effect of Soil and Foliar Application of Plant Nutrients on Purple Blotch and Tip-Burn of Onion (Bangladesh Journal of Agricultural Research, 2023)
An experiment was conducted in the field of Plant Pathology Division, BARI, Cazipur, during Robi 2015-16, 2016-17 and 2017-18 cropping seasons to evaluate the efficacy of available plant nutrients against purple blotch disease and tip-burn of onion. Eight different plant nutrients viz. Potassium (ZnSO4 fertilizer), Phosphorus (TSP fertilizer), Boron (Boron fertilizer), Zinc (ZnSO4 fertilizer), Calcium (CaSO4 fertilizer), Copper (CuSO4), Silicon (silica gel) and Manganese (MnSO4 fertilizer) were tested against purple blotch disease and tip-burn of onion. Soil and foliar application of plant nutrients viz. Potassium, Phosphorus, Boron, Zinc, Calcium, Copper, Silicon and Manganese in the formed of water solution gave appreciable reduction of purple blotch disease and tip-burn incidence and increased plant growth such as shoot and root growth as well as yield of onion. Among the nutrients solution Potassium, Phosphorus, Silicon, Zinc and Calcium were performed better for reducing purple blotch disease severity (upto 62.78%), tip-burn incidence (upto 72.22%) and increasing plant growth as well as yield of onion. Application of Boron and Manganese also performed better than control. So, soil and foliar application plant nutrients viz. Potassium, Phosphorus, Silicon, Zinc, Boron and Manganese might be recommended for tip-burn and purple blotch disease management and also for onion production in Bangladesh.Bangladesh J. Agril. Res. 46(2): 153-165, June 2021